An optimized regulating method for composting phosphorus fractions transformation based on biochar addition and phosphate-solubilizing bacteria inoculation. (December 2016) - Wei, Yuquan; Zhao, Yue; Wang, Huan; Lu, Qian; Cao, Zhenyu; Cui, Hongyang; Zhu, Longji; Wei, Zimin
Graphical abstract: Highlights: Assess the concentration and distribution of P fractions in different treatments. Analyze microbial biomass and bacterial diversity during composting. Confirm the relation of bacterial community and environmental factors and treatments. Suggest the combination of PSB and biochar to improve the inoculation effect. An optimized regulating method for the distribution of P fractions was proposed. Abstract: The study was conducted to investigate the influence of biochar and/or phosphate-solubilizing bacteria (PSB) inoculants on microbial biomass, bacterial community composition and phosphorus (P) fractions during kitchen waste composting amended with rock phosphate (RP). There were distinct differences in the physic-chemical parameters, the proportion of P fractions and bacterial diversity in different treatments. The contribution of available P fractions increased during composting especially in the treatment with the addition of PSB and biochar. Redundancy analysis showed that bacterial compositions were significantly influenced by P content, inoculation and biochar. Variance partitioning further showed that synergy of inoculated PSB and indigenous bacterial communities and the joint effect between biochar and bacteria explained the largest two proportion of the variation in P fractions. Therefore, the combined application of PSB and biochar to improve the inoculation effect and an optimized regulating method were suggested based on the distribution of P fractions.